2016
DOI: 10.1039/c5nj03202d
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane foams doped with stable silver nanoparticles as bactericidal and catalytic materials for the effective treatment of water

Abstract: The development of reusable dual-purpose nanocomposite foams for catalytic and bactericidal water treatment is reported. Small non-aggregated silver nanoparticles were made using Intermatrix Synthesis inside a polyurethane foam, which was chosen as a suitable polymeric matrix due to its high chemical and mechanical stability and industrial applicability. The antibacterial activity of the obtained nanocomposites was evaluated against suspensions of Gram-negative bacteria (E. coli), showing ideal bactericidal fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The peaks appearing at 2272, 2969, and 3272 cm −1 are ascribed to the presence of the −NCO, C−H, and N−H functional groups in PUF. 40 Interestingly, there is a significant red-shift of 54 cm −1 in the NCO peak upon loading of Pd NPs on PUF while all the other peaks remain unchanged (Figure 5h), suggesting that binding of Pd to the foam involves the NCO bond of polyurethane. The red-shift is attributed to partial donation of an oxygen lone pair to Pd, which weakens the NCO bond in the Pd-loaded PUF.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The peaks appearing at 2272, 2969, and 3272 cm −1 are ascribed to the presence of the −NCO, C−H, and N−H functional groups in PUF. 40 Interestingly, there is a significant red-shift of 54 cm −1 in the NCO peak upon loading of Pd NPs on PUF while all the other peaks remain unchanged (Figure 5h), suggesting that binding of Pd to the foam involves the NCO bond of polyurethane. The red-shift is attributed to partial donation of an oxygen lone pair to Pd, which weakens the NCO bond in the Pd-loaded PUF.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…They can be recycled or recovered after use to reduce production costs and increase material utilization efficiency [3]. Thermosetting polymers like PU foams are widely preferred due to their light weight, excellent biocompatibility, flexible mechanical properties, and the presence of a urethane linkage (–NH–CO–O–) that bonds easily with nanoparticles such as silver nanoparticles (AgNPs) [4,5,6,7,8,9,10]. Also, PU foams have the capability of delivering a wide range of cell structures, rigidity, strength, and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Many publications [4,6,12,21,23,24,25] have demonstrated that PU foams exhibit high stability against chemical degradation, high mechanical durability, significant cushion properties, good swelling behavior, ease of separation from a solution, and are also some of the most inexpensive available polymer products. Several two-dimensional, relatively expensive, low-throughput, and complex imaging tools have been used for porous material characterization including optical microscopy, scanning electron microscopy (SEM), field emission SEM (FESEM), and transmission electron microscopy (TEM) [26].…”
Section: Introductionmentioning
confidence: 99%
“…These properties can be modified for specific applications just by changing the formulation and adjusting the reaction conditions during the preparation procedure and, interestingly, their physical and chemical characteristics can be improved through a combination of various additives during the synthesis (polymerization) process . Specifically, the incorporation of nanomaterials (i.e., metal nanoparticles, NPs) could significantly improve the properties of PU materials and their further applicability …”
Section: Introductionmentioning
confidence: 99%
“…However, their mechanism of action is not yet clearly understood, and a suggested mechanism of Ag NPs cytotoxicity toward the bacterial cell is presented in Figure . Silver is a noble metal with high biocompatibility, electrical and thermal conductivity, and excellent resistance to oxidation, which gives it various applications such as an antimicrobial filters, medical devices, protective cloths, chemical sensors, and water disinfectants …”
Section: Introductionmentioning
confidence: 99%